The impact of cyclone aila on the sundarban forest ecosystem - Rahman, Shafiqur M.A.; Rahman, Hafizur Z.; Shahid, Shamsuddin; Khan, Rehanullah; Jahan, Nusrat A.; Ahmed, Zafar U.; Khanum, R.; Ahmed, Manzoor F.; Mohsenipour, Morteza (© 2017 CESER Publications, 2018)
This article was published in the International Journal of Ecology and Development [© 2017 by International Journal of Ecology & Development.] The Article's website is at: http://www.ceser.in/ceserp/index.php/ijed/article/view/4771